SOCIO-CULTURAL CONTENT OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN INNOVATIVE SOCIETY - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article analyzes the formation and perspectives of development of information and communication technologies as an important part of an innovative society and focuses on socio-cultural content of such technologies.